Desemprego: experiências de transição - Santos, Eduardo J. Ribeiro (2010)
Work appears as an important determinant in psychological health and well-being (Blustein, 2008). However, the current structure of the labor market is complex, unpredictable and unstable, making it necessary to rethink the meaning of work in human existence. This article focuses on the different types of transitions (voluntary vs. involuntary) as well on the different reactions to unemployment, and presents some intervention strategies in the context of career counseling, conceived as a (possible) response to changes in employment.